Gray matter correlates of pressure pain thresholds and self-rated pain sensitivity: a voxel-based morphometry study. Issue 7 (July 2018) - Ruscheweyh, Ruth; Wersching, Heike; Kugel, Harald; Sundermann, Benedikt; Teuber, Anja
Abstract : Abstract: Individual differences in sensitivity to pain are large and have clinical and scientific importance. Although heavily influenced by situational factors, they also relate to genetic factors and psychological traits, and are reflected by differences in functional activation in pain-related brain regions. Here, we used voxel-based morphometry to investigate if individual pain sensitivity is related to local gray matter volumes. Pain sensitivity was determined using (1) index finger pressure pain thresholds (PPTs) and (2) pain intensity ratings of imagined painful situations as assessed by the Pain Sensitivity Questionnaire (PSQ) in 501 population-based subjects participating in the BiDirect Study. Pain Sensitivity Questionnaire scores were positively associated with gray matter in 2 symmetrical clusters, with a focus on the parahippocampal gyrus, extending to the hippocampus, fusiform gyrus, BA19, putamen, and insula ( P < 0.05 corrected), but the effect was small ( R 2 = 0.045-0.039). No negative associations with the PSQ and no associations with the PPT reached significance. Parahippocampal activation during pain and altered parahippocampal gray matter in chronic pain have been reported, which would be consistent with positive associations with PSQ scores. Alternatively, associations of PSQ scores with the parahippocampal and fusiform gray matter could relate to the visual imagination of painful situations required by the PSQ, not to pain sensitivity itself. Regarding PPTs, the present data obtained in a large sample strongly suggest an absence of associations of this parameter with gray matter volume. In conclusion, the present results argue against a strong association between pain sensitivity and local gray matter volumes. Abstract : Pain Sensitivity Questionnaire scores, but not pressure pain thresholds were positively correlated with gray matter volume with a focus on the parahippocampal gyrus.